2019
DOI: 10.1186/s13063-019-3492-3
|View full text |Cite
|
Sign up to set email alerts
|

Do antibacterial skin sutures reduce surgical site infections after elective open abdominal surgery? - Study protocol of a prospective, randomized controlled single center trial

Abstract: Background Surgical site infections (SSI) remain one of the most common complications in conventional abdominal surgery with an incidence between 4% and 19% (Sandini et al., Medicine (Baltimore) 95:e4057, 2016) in the literature. It is unclear whether the use of coated suture material for skin closure reduces the risk of SSI. In line with in-vitro results, we hypothesize that the use of antibacterial skin sutures (triclosan-coated poliglecaprone 25) reduces the rate of SSI after open abdominal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Although orthopedic surgeons have controlled and eradicated infections by including preventive use of antibiotics and strict aseptic practice, they still cannot completely eliminate the occurrence of infections. [19] Many studies [20][21][22] have shown that many factors contribute to the occurrence of SSIs after surgery, and the choice of suture is also one of them. [6,23] Recent laboratory and clinical studies have also revealed that can adhere to braided sutures and form a biofilm-like structure.…”
Section: Discussionmentioning
confidence: 99%
“…Although orthopedic surgeons have controlled and eradicated infections by including preventive use of antibiotics and strict aseptic practice, they still cannot completely eliminate the occurrence of infections. [19] Many studies [20][21][22] have shown that many factors contribute to the occurrence of SSIs after surgery, and the choice of suture is also one of them. [6,23] Recent laboratory and clinical studies have also revealed that can adhere to braided sutures and form a biofilm-like structure.…”
Section: Discussionmentioning
confidence: 99%
“…The primary source of surgical site infection is contamination of the wound and inadequate wound disinfection prior to surgical closure. The role of antimicrobial sutures in preventing surgical site infection remains critical to address antimicrobial resistant pathogens [11][12][13][14]. The material of the surgical suture participates in bacteria adhesion and formation biofilm on its surface and becomes resistant to conventional antimicrobial drugs [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a growing demand for suture materials as surgical procedures are increasing in number and because material requirements differ for each procedure [168]. Work is underway to develop second-generation sutures displaying bioactive functionalities, i.e., antimicrobial sutures for preventing surgery-associated infections [169] or absorbable sutures. Microbial polymers have found a niche in this field due to their tensile properties, which help to resist tissue-induced stress, and because of their ease of functionalization.…”
Section: Sutures and Biological Gluesmentioning
confidence: 99%